The dimensionality of the Conflict Resolution Styles Inventory across age and relationships - Trifan, Tatiana Alina; Meeus, Wim; Branje, Susan (Frontiers in Psychology, 2024)
Close interpersonal conflicts between parents and children, marital or romantic partners, and between friends are common, and adjustment in youth and adults depends on how these conflicts are managed. While conflict management is important for relationships and adjustment, the structure of conflict management in adults or in youths has rarely been examined. Knowing how conflict management is structured, and whether this structure changes with age and relationships, is important to understanding what factors influence the development of conflict management skills, and how to intervene. In the current study, we explored the unidimensional vs. multidimensional structure of conflict management in family relationships, friendships and romantic relationships across adolescence and adulthood. The sample consisted of 497 Dutch adolescents (57% boys, Mage = 13.03, SD = 0.46, 11–15 years old) who were followed over 11 years in 9 measurement waves, and their parents, siblings, best friends (six waves), and romantic partner (three waves). First-order factor analyses (CFA) showed that the structure of conflict management is similar for adolescents and adults, across relationships. The results of second-order models, including the theoretical higher dimensions positive/negative conflict management and engagement/disengagement, showed no support for these higher dimensions. The results of bifactor models showed differences between adults and youths: while positive problem solving was part of the general factor of conflict management in adults, it was not part of this general factor in adolescents. The general factor was linked to increases in internalizing and externalizing problems, and with decreases in prosocial behavior. Overall, the bifactor models increased the interpretability and validity of the conflict management measure.